Groundwater Monitoring System Using Internet of Things. Issue 1 (September 2020) - SachinAmreiss, GN.; Karthikeyan, B.; Premkumar, K.
Abstract: The major problem among the people is that they are lacking in the awareness of the underground water usage. Thus, they are in the process of designing the "Application" which gives the data about the underground water consumption of the consumers and monitor the ground water usage of the consumers. Also, alarming when the maximum usage of water or wastage of water. This system sends the information of the water usage of that area and automatically recorded in the government water board of that area with quantity of the water usage, If exceeds the limit will have the locking system of the water supply of the usage area with fine. Thus the paper gives the total guidance to the people according the usage of the underground water resources digitally with the application itself